2007
DOI: 10.1093/jmedent/44.6.903
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Comparison of External Morphology of Immature Stages of Lutzomyia (Nyssomyia) intermedia and Lutzomyia (Nyssomyia) whitmani (Diptera: Psychodidae), Vectors of Cutaneous Leishmaniasis, by Scanning Electron Microscopy

Abstract: Lutzomyia (Nyssomyia) intermedia (Lutz & Neiva 1912) and Lutzomyia (Nyssomyia) whitmani (Antunes & Coutinho 1939) (Diptera: Psychodidae) are vectors of American cutaneous leishmaniasis in several endemic regions of Brazil. We analyzed the external morphological aspects of the immature stages of these two vectors by using scanning electron microscopy. In general, the larval stages of the two species are morphologically similar, although some differences were noted. Detailed examination of the eggs of both speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 35 publications
0
24
1
Order By: Relevance
“…whitmani and Lu. intermedia (Bahia et al, 2007), although in this study, the pattern of pores not was observed. However, Bahia et al (2007) and Pessoa et al (2001) report the presence of pores in these filaments.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…whitmani and Lu. intermedia (Bahia et al, 2007), although in this study, the pattern of pores not was observed. However, Bahia et al (2007) and Pessoa et al (2001) report the presence of pores in these filaments.…”
Section: Discussioncontrasting
confidence: 69%
“…whitmani and Lu. intermedia (Bahia et al, ), although in this study, the pattern of pores not was observed. However, Bahia et al .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…However, none of the published information reports the successful colonization of sand flies under laboratory setup in Sri Lanka. e morphology of Phlebotomine sand flies including P. argentipes has been reported by several studies [15][16][17]. Although these reports provide valuable information to identify each stage of sand fly life cycle, identification of each instar of sand fly larvae still remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The use of scanning electron microscopy (SEM) has significant improved the characterization and descriptions of immature forms, and provided details of larval chaetotaxy [4,5]; ontogeny [6][7][8]; spiracles [9,10]; antennal, and mouthparts, such as the sensilla as well as caudal bristles [7,11,12]. Despite this, only a few articles have been carried out about the pupal morphology of New World phlebotomine sand flies [8,[13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%